Efektifitas Air Rebusan Simplisia Daun Binahong (Anredera Cordifolia) Terhadap Penyembuhan Luka Perineum Pada Ibu Nifas Di PMB K Tahun 2024 - Utami, Monica Bella Putri; Yuniawati, Desi (Bunda Edu-Midwifery Journal (BEMJ), 2024)
Background: Perineal wounds are a condition where the continuity of the perineal tissue is disrupted which occurs in almost all deliveries. If this situation is not handled properly, wound healing can take a long time and infection can occur. Purposed: To determine the effectiveness of boiled water from simplicia leaves of binahong (Anredera Cordifolia) on healing perineal wounds in PMB K mothers in 2024. Research Methods: The research design used a quasi experiment with a posttest only approach with control group design. The population was 50 people with a purposive sampling technique with a sample of 25 people in the experimental group and 25 people in the control group. The research instrument used the REEDA scale. Data analysis was univariate with frequency distribution and bivariate using the Mann Whitney test. Results: Most of the healing of perineal wounds in the group that consumed boiled water from simplicia leaves of binahong (Anredera Cordifolia) was good, 22 people (88%), while in the control group more than half of the wounds healed well, 14 people (56%). Giving simplicia decoction of binahong leaves (Anredera Cordifolia) is effective in healing perineal wounds in postpartum mothers (p-value 0.013<0.05). Conclusion: Giving simplicia decoction of binahong leaves (Anredera Cordifolia) is effective in healing perineal wounds in postpartum mothers.